Student misbehavior and teacher well-being: Testing the mediating role of the teacher-student relationship - Aldrup, Karen; Klusmann, Uta; Lüdtke, Oliver; Göllner, Richard; Trautwein, Ulrich (Learning and instruction, 2018)
Asked about major job stressors, teachers consistently name classroom disturbances or disciplinary problems. Furthermore, student misbehavior has been linked to reduced occupational well-being. However, there is a pressing need to uncover the psychological processes explaining this association. In their model of teacher well-being, Spilt, Koomen, and Thijs (2011) suggested the teacher-student relationship as a mediator. To test this assumption, the present study used longitudinal data from N = 222 teachers who rated student misbehavior in their classroom, the teacher-student relationship, and their well-being in terms of emotional exhaustion and work enthusiasm. In addition, the teachers’ students (N = 4111) were asked about behavior problems in their class. The results revealed links between teacher-rated student misbehavior, increased exhaustion, and decreased enthusiasm. Student-rated misbehavior was correlated with teacher well-being to a lesser extent. Furthermore, the teacher-student relationship was positively associated with teacher well-being and mediated the link between teacher-perceived misbehavior and enthusiasm. (Orig.).